Germline testing for homologous recombination repair genes: opportunities and challenges - Hirsch, Steffen; Gieldon, Laura; Sutter, Christian; Dikow, Nicola; Schaaf, Christian P. (Genes, chromosomes & cancer, 2021)
Pathogenic variants in the BRCA1 and BRCA2 genes are well known causes of hereditary breast and ovarian cancer. Other genes involved in the homologous recombination pathway can also be associated with increased probability of cancer development, for example, breast and ovarian cancer, prostate and pancreatic cancer, colorectal cancer, and even childhood tumors like medulloblastoma. Traditionally, patients and families likely to harbor a genetic predisposition have been identified using personal and family history. Several checklists and risk prediction tools have proven to be useful in the clinic. Through the widespread application of next generation sequencing of tumor tissue, a growing number of individuals with genetic cancer predisposition is now identified molecularly, even in the absence of a suggestive family history. Any constitutional variant identified during molecular genetic testing has to be assessed for its relevance, both functionally and in the context of patient phenotype. Variant curation is time consuming, but has been increasingly standardized by introduction of several guidelines to allow reliable and reproducible classification of constitutional variants. Variant classification by expert panels using data mining tools, evidence-based decision trees and gene specific criteria represents the gold standard. Participation of geneticists in molecular tumor boards facilitates the curation of potential constitutional variants, germline validation and thus directing the patient to appropriate counselling and care pathways. Due to the high relevance of germline variants for treatment and surveillance of the index patient and predictive testing and surveillance of relatives, only pathogenic or likely pathogenic variants must be used for clinical decision-making.
First published: 20 October 2020
Gesehen am 06.12.2021